2016
DOI: 10.1523/jneurosci.3634-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebral Network of Parkinson's Tremor: An Effective Connectivity fMRI Study

Abstract: Parkinson's resting tremor has been linked to pathophysiological changes both in the basal ganglia and in a cerebello-thalamo-cortical motor loop, but the role of those circuits in initiating and maintaining tremor remains unclear. Here, we test whether and how the cerebello-thalamo-cortical loop is driven into a tremor-related state by virtue of its connectivity with the basal ganglia. An internal replication design on two independent cohorts of tremor-dominant Parkinson patients sampled brain activity and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 68 publications
9
131
1
1
Order By: Relevance
“…In PD, epilepsy is considered as an uncommon comorbidity in a few available studies (Vercueil, 2006), but also see: Son et al (2016). However, Parkinson's resting tremor is definitely induced by paroxysmal synchronous activity of the cerebello-thalamocortical network (Hallett, 2014;Singh et al, 2016), is likely initiated in motor cortex (Dirkx et al, 2016) and represents a harmful example of rhythmic collective dynamics of large brain cell networks resembling the epileptic ones (Velazquez et al, 2015).…”
Section: Neuronal Hyperactivitymentioning
confidence: 99%
“…In PD, epilepsy is considered as an uncommon comorbidity in a few available studies (Vercueil, 2006), but also see: Son et al (2016). However, Parkinson's resting tremor is definitely induced by paroxysmal synchronous activity of the cerebello-thalamocortical network (Hallett, 2014;Singh et al, 2016), is likely initiated in motor cortex (Dirkx et al, 2016) and represents a harmful example of rhythmic collective dynamics of large brain cell networks resembling the epileptic ones (Velazquez et al, 2015).…”
Section: Neuronal Hyperactivitymentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies clearly demonstrated that the activation at the level of the prefrontal cortex and the globus pallidus was reduced in patients with NT-PD compared to those with TD-PD and controls [Prodoehl et al, 2013]. On the other hand, in TD-PD patients, cerebral activity related to tremor first arised in the internal globus pallidus and was then propagated to the cerebello-thalamo-cortical loop, the "dimmer-switch hypothesis" [Dirkx et al, 2016;Helmich et al, 2011Helmich et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the limited number of investigations addressing the role of cerebro-cerebellar circuit in language network reorganization following supratentorial lesion (Lidzba, Wilke, Staudt, Krageloh-Mann, & Grodd, 2008), similar studies have been extensively performed in the investigation of various higher-order cognitive functions in healthy subjects, and patients with neurodegenerative, neurodevelopmental, neurological, and psychiatric diseases (Buckner, 2013;Buckner, Krienen, Castellanos, Diaz, & Yeo, 2011;Dirkx et al, 2016;Guo et al, 2016;Kim et al, 2014;Marien et al, 2014Marien et al, , 2009O'Callaghan et al, 2016;Schmahmann and Sherman, 1998). In healthy subjects, task-fMRI research on the functional topography of human cerebellum revealed that the activation areas for language were mainly located in lobule VI and Crus I with a prominently rightlateralizing pattern, which reflected crossed organizational arrangement of cerebro-cerebellar circuit (Stoodley and Schmahmann, 2009;Stoodley, Valera, & Schmahmann, 2012).…”
mentioning
confidence: 99%